Osseo integrated finger prosthesis with a custom abutment - Benny Thomas; Chalakuzhiyil Abraham Mathew; Mahendra Perumal; Maheshwaran Marappan (Wolters Kluwer Medknow Publications, 2017)
One of the most regularly encountered forms of partial hand loss causing physical, psychosocial and financial burden to an individual is the finger amputation followed by trauma. The prosthetic rehabilitation of amputated finger is a good treatment option, when compared to all other means of complex and unaffordable options. Osseointegrated implant retained silicone finger prosthesis with innovative prosthetic designs can provide the patient a life changing experience.